Enhancing consistency of AHP-based expert judgements: A new approach and its implementation in an interactive tool - Shimon Frish; Irit Talmor; Omer Hadar; Maxim Shoshany; Aviad Shapira (MethodsX)
The analytic hierarchy process is an effective method for simplifying complex decision-making processes involving multiple criteria. Experts convey their criteria evaluations through pairwise comparisons that ultimately result in a consistency check of the preferences obtained. However, achieving a predetermined consistency ratio (CR) threshold is challenging for such problems, which may compromise the reliability of expert evaluations. To address this issue, this paper presents a novel interactive software tool designed to enhance the logical coherence of expert judgments during decision-making processes. Utilizing a sophisticated greedy algorithm, which is interactively run vis-à-vis the experts in real time, the tool detects inconsistencies and suggests minor adjustments to improve the CR while preserving the integrity of the original evaluations. In a case study of border delineation, in which 21 senior officials involved in international border negotiations evaluated six criteria, the tool successfully reduced the CR values to the minimum required, significantly improving the consistency and reliability of the evaluations. The proposed tool has broad potential applications in various complex decision-making scenarios. In future developments, the tool could also be adapted to incorporate clustering techniques for managing complex criteria sets, or extended to support group decision making by assessing consensus levels and recommending minimal adjustments. • AHP-based pairwise comparisons of n criteria by experts are recorded in an n × n reiprocal preference matrix whose eigenvalu λmax is used to compute the consistency ratio (CR) of the resulting priority vector. • An iterative greedy algorithm developed to enhance the consistency of the solution in case CR>10% enforces minimal intervention by limiting the adjustment to single-step modifications on unaltered pairwise comparisons only. • The algorithm is implemented in an interactive, user-friendly software tool, ensuring transparency and expert engagement through real-time, traceable consistency refinement.